Risk Factors Of Hypertension In Jambi City Based On Sehat Indonesiaku Application (Asik) Data In 2023 - Romanti Simbolon; Rd. Halim; Ashar Nuzulul Putra; Ummi Kalsum; Muhammad Syukri (International Journal of Health Engineering and Technology, 2025)
Hypertension is a global health problem as it causes high morbidity and mortality, with approximately 9.4 million deaths every year. This condition shows that hypertension remains a significant health burden. The aim of this study was to identify the factors associated with the incidence of hypertension in Jambi City. This research is a secondary data analysis with a cross-sectional design, using data from the Sehat Indonesiaku Application (ASIK) in 2023, conducted from August 2024 to May 2025. The sample included all individuals aged ≥ 15 years recorded in the ASIK application, selected using a total sampling technique. Data were analyzed using Chi-Square tests and Logistic Regression to identify risk factors. The proportion of hypertension among individuals aged ≥ 15 years was 35.2%. Variables significantly associated with hypertension among those aged ≥ 15 years were sex [Adj PR = 1.09; 95% CI: 1.01–1.17], age ≥ 40 years [Adj PR = 3.82; 95% CI: 3.53–4.13], physical activity [Adj PR = 0.82; 95% CI: 0.75–0.88], fruit and vegetable consumption [Adj PR = 0.89; 95% CI: 0.83–0.96], salt consumption [Adj PR = 1.56; 95% CI: 1.41–1.73], and obesity [Adj PR = 1.94; 95% CI: 1.80–2.10]. Age is the most influential factor for hypertension incidence; therefore, the community is advised to limit salt intake, maintain a healthy nutritional status to prevent obesity, and increase physical activity, especially among men aged ≥ 40 years.